No effect of acute and 6-day nitrate supplementation on VO2 and time-trial performance in highly trained cyclists - Nyakayiru, J. M.; Jonvik, K. L.; Pinckaers, P. J. M.; Senden, J.; van Loon, L. J. C.; Verdijk, L. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
While the majority of studies reporting ergogenic effects of dietary nitrate have used a multiday supplementation protocol, some studies suggest that a single dose of dietary nitrate before exercise can also improve subsequent performance. We aimed to compare the impact of acute and 6-day sodium nitrate supplementation on oxygen uptake (VO2) and time-trial performance in trained cyclists. Using a randomized, double-blind, cross-over design, 17 male cyclists (25 ± 4 y, VO2peak 65 ± 4 ml·kg-1·min-1, Wmax 411 ± 35 W) were subjected to 3 different trials; 5 days placebo and 1 day sodium nitrate supplementation (1-DAY); 6 days sodium nitrate supplementation (6-DAY); 6 days placebo supplementation (PLA). Nitrate was administered as 1097 mg sodium nitrate providing 800 mg (~12.9 mmol) nitrate per day. Three hours after ingestion of the last supplemental bolus, indirect calorimetry was performed while subjects performed 30 min of exercise at 45% Wmax and 30 min at 65% Wmax on a cycle ergometer, followed by a 10 km time-trial. Immediately before exercise, plasma [nitrate] and [nitrite] increased to a similar extent during the 6-DAY and 1-DAY trial, but not with PLA (plasma nitrite: 501 ± 205, 553 ± 278, and 239 ± 74 nM, respectively; p < .001). No differences were observed between interventions in VO2 during submaximal exercise, or in time to complete the time-trial (6-DAY: 1004 +/- 61, 1-DAY: 1022 ± 72, PLA: 1017 ± 71 s; p = .28). We conclude that both acute and 6-days of sodium nitrate supplementation do not alter V?O2 during submaximal exercise or improve time-trial performance in highly trained cyclists, despite increasing plasma [nitrate] and [nitrite].